Organic Farming and Women Empowerment in Karnali Province, Nepal (Surkhet Journal, 2025)
This study examines the factors influencing women’s empowerment in organic farming in Karnali Province, Nepal, focusing on education, market access, institutional policies, technology, infrastructure and socio-cultural dynamics. A quantitative approach was employed, utilizing standardized Likert scale questionnaires to collect data from 200 women actively engaged in organic farming. Smart PLS path analysis and reliability tests were applied to assess variable relationships. The target population comprised women organic farmers in Karnali Province. A sample of 200 participants was selected through purposive sampling, ensuring representation of diverse backgrounds and farming experiences. Education and training significantly enhanced women’s skills and confidence in organic farming, Access to resources was critical for empowerment, Supportive policies and gender-sensitive institutions  promoted women’s participation, Socio-cultural barriers like gender norms, hindered empowerment but could be addressed through targeted interventions and Infrastructure, technology and market access improved productivity and economic growth. The study highlights the need for holistic strategies i.e. policy reforms, training programs and cultural shifts to empower women in organic farming, fostering sustainable agricultural development. Further studies could explore longitudinal impacts of interventions, regional comparisons or qualitative insights into women’s lived experiences in organic farming.